The Numerical Simulation of the Transient Plane Heat Source Method to Measure the Thermophysical Properties of Materials - Jianyuan Sun; Siwen Zhang; Pengcheng Shi; Zao Yi; Yougen Yi; Qingdong Zeng (Applied Sciences)
The transient plane heat source method (TPS), also known as the hot disc method, is an experimental method for determining the thermal transport properties of materials. The method’s main element is a sensor made of a nickel metal strip in the shape of a double helix, which is inserted into an insulating polymer film. In this work, we used the finite element method to create a three-dimensional model of the sensors and compared the simulated and experimentally recorded mean temperature rise data. The volume mean temperature rise of the sensor, as determined through simulation, exhibits a high level of resemblance with the corresponding experimental data. Additionally, temperature rise curves of several other materials are also simulated based on the model and the thermal performance parameters are calculated from these data. In the meantime, this paper presents an evaluation and discussion of the current density distribution of the sensor and the temperature distribution during the testing of the sample. This simulation has the potential to be utilized for future geometry and parameter estimate optimization, and provides a theoretical reference for detector design.